2018
DOI: 10.1073/pnas.1722426115
|View full text |Cite
|
Sign up to set email alerts
|

Internal states and extrinsic factors both determine monkey vocal production

Abstract: A key question for understanding speech evolution is whether or not the vocalizations of our closest living relatives-nonhuman primates-represent the precursors to speech. Some believe that primate vocalizations are not volitional but are instead inextricably linked to internal states like arousal and thus bear little resemblance to human speech. Others disagree and believe that since many primates can use their vocalizations strategically, this demonstrates a degree of voluntary vocal control. In the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 50 publications
7
74
0
Order By: Relevance
“…Turning first to primates, both monkeys and apes display relevant behavior. Marmosets, a New World monkey who engages in turn taking [62], uses different proportions of affiliative call types depending on social distance [63], as well as loudness relative to physical distance [64]. They can also convey identity through aspects of their calls [65].…”
Section: Box 3 Evidence Of Vocal Learning Abilities In Species Outsimentioning
confidence: 99%
“…Turning first to primates, both monkeys and apes display relevant behavior. Marmosets, a New World monkey who engages in turn taking [62], uses different proportions of affiliative call types depending on social distance [63], as well as loudness relative to physical distance [64]. They can also convey identity through aspects of their calls [65].…”
Section: Box 3 Evidence Of Vocal Learning Abilities In Species Outsimentioning
confidence: 99%
“…Vocal flexibility during perturbing noise in marmoset monkeys. Current studies have control when [14], where [38], and what to vocalize [39]. In addition, recent studies revealed 232 that marmosets are able to modulate distinct call parameters in response to acoustic 233 feedback [18,40].…”
Section: Monkeys 190mentioning
confidence: 99%
“…Hence, it is plausible that the ability to associate emotional content to specific changes in the voice, which goes beyond the association between discrete units and their denotation, constitutes a fundamental evolutionary precursor of language. Future research shall further address this line of investigation, which will advance the study of the evolutionary vocal precursors of language, placing it into a fruitful perspective (see Liao, Zhang, Cai, & Ghazanfar, 2018).…”
Section: Biologically Universal Meanings At the Origins Of Languagementioning
confidence: 99%
“…Recent research on marmoset monkeys (Callithrix jacchus) investigated whether monkey calls are automatic reflexes intrinsically linked to internal states such as emotional arousal, or whether they result from a degree of volitional vocal control, and can thus be strategically used to manipulate the listeners' reactions (Liao et al, 2018). Interestingly, the authors found that physical distance from a conspecific and visual access to her/him affected the level of arousal, resulting into different vocal behaviors.…”
Section: Concluding Remarks: Social Interactions At the Origins Of Lamentioning
confidence: 99%